Program for the Neuropsychological Stimulation of Cognition in Students: Impact, Effectiveness, and Transfer Effects on Student Cognitive Performance - Cardoso, Caroline de Oliveira; Seabra, Alessandra Gotuzo; Gomes, Cristiano Mauro Assis; Fonseca, Rochele Paz (Frontiers in Psychology, 2019)
Despite the crucial role played by the executive functions (EF) to cognitive, emotional, and social development of children before and during school years, little attention has been given to construct and analyze the efficacy of programs which intend to develop them. The Program of Neuropsychological Stimulation of Cognition in Students: emphasis on Executive Functions, or PENcE, is an early and preventive intervention program for school-aged children, implemented at school, 3 times a week for 5 months. The PENcE was structured in 4 modules, each focusing on a different executive component: Organization and Planning; Inhibitory Control; Working Memory; Cognitive Flexibility. The objective of this study was to verify the effectiveness of the PENcE among Elementary School children, and to investigate whether there are transfer effects to other executive, cognitive, and academic abilities. The sample consisted of 113 children attending 3rd or 4th grade at two public elementary schools. Eight classes participated in the study, divided into two groups: an experimental group (EG) (four classes; n=64), which received the intervention, and a control group (CG) (four classes; n=49), which continued their regular school activities. The executive functions and academic skills of both participant groups were evaluated before and after the intervention. The EG showed significantly greater improvements in inhibitory control, working memory, and abstract planning relative to the CG, with a small to medium effect size. There were transfer effects to other cognitive and academic abilities. These findings suggest the PENcE may be a useful method of improving executive functions, and could benefit both school-aged children and education professionals.